Challenges in GIS practice in Geography teacher training during COVID 19 pandemic: Students' perspective from private Islamic university in Indonesia - Anang Widhi Nirwansyah (Universitas Negeri Malang, 2022)
During the COVID 19 pandemic, a vast number of universities need to limit their face-to-face teaching activities, including laboratory access. For Geography education students, this situation forced them to use Geographic Information System (GIS) as a major skill set in a virtual learning model, even only with minimum infrastructures such as laptops, mobile phones, and unstable internet connections. In the current study, the perception of undergraduate students from the Geography teaching program at Universitas Muhammadiyah Purwokerto, Central Java, Indonesia, about the effectiveness and readiness of online learning platforms as the impact of the global pandemic were examined. The results showed that students were relatively satisfied and motivated in GIS online learning modules, although classical learning was still preferable. Nevertheless, some students were facing electricity and unstable internet connectivity issues. Finally, in the future, distance learning for GIS teaching programs should be integrated at the national level with sufficient infrastructure support, including supporting training on developing modules and evaluation to increase the student learning experience.